PENGARUH KOMPETENSI, MOTIVASI DAN REWARD TERHADAP KINERJA KARYAWAN PT. PAMA PERSADA NUSANTARA KUTAI TIMUR - Febrianti, Santi; Yusuf , Tamzil; Hernadi Moorcy , Nadi (Fakultas Ekonomi Universitas Balikpapan, 2025)
This research aims to determine the influence of competence, motivation, and reward variables on the performance of employees at PT. Pama Persada Nusantara Kutai Timur. The population used in this study were employees of PT Pama Persada Nusantara Kutai Timur, totaling 420 employees. The sample used in this study was 81 respondents with a non-probability sampling technique. This is a quantitative study. The analytical tool used is multiple linear regression. The results of the analysis show that partially, competence has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, and 1 reward has a positive and significant effect on the performance of employees of PT. Pama Persada Nusantara Kutai Timur.